KEEFEKTIPAN PEMBELAJARAN MATEMATIKA REALISTIK (PMR) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS I SD - Darnis, Darnis (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
Mathematics teaches students logical thinking, analysis, synthesis, critical, and creative. As high as students are able to work together in solving the problems faced. To achieve all of that we need an effective learning process, one of which is by applying realistic mathematical learning. The background of this research is the low learning outcomes of mathematics in grade I students of SD Negeri 019 Bumi Ayu. The purpose of this study is to improve student mathematics learning outcomes. The form of research used is classroom action research. The study was conducted in 2 cycles, each through the stages of planning, implementation, observation, and reflection. The results of the study showed the basic score of students completeness was 46.1%, the percentage of completeness in cycle I was 73%, and the percentage of completeness in cycle II was 92.3%. On the basic score the number of students who completed was 12 people, while the number of students who did not complete was 14 people. In the first cycle the number of students who completed was 19 people, while the number of students who did not complete was 7 people. In cycle II the number of students who completed was 24 while the number of students who did not complete was 2 people. Based on the data obtained above, it can be concluded that by applying realistic mathematics learning (PMR) can improve the learning outcomes of grade I students of SD Negeri 019 Bumi Ayu